Notch1 controls cell chemoresistance in small cell lung carcinoma cells - Hassan, Wael Abdo (Thorac Cancer, 2015)
BACKGROUND: Small cell lung carcinoma (SCLC) is characterized by a high rate of relapse and failure of chemotherapy because of the emergence of drug resistant cells. Notch signaling controls carcinogenesis in several human malignancies and could be involved in the resistance of cells to several chemotherapeutic agents. Herein, we analyzed the role of Notch1 signaling in the resistance of human SCLC cells to doxorubicin. METHODS: Small interfering ribonucleic acid technology was used to knock down (KD) Notch1 in H69AR and SBC‐3 SCLC cells. We detected the effect of inhibiting Notch1 on the expression of drug resistant related molecules: multidrug resistance‐associated protein (MRP‐1) and anti‐apoptotic factor B‐cell lymphoma‐2, as well as to cell adhesion molecule E‐cadherin, which contributes to the adhesion of SCLC cells to the extracellular matrix and confers chemoresistance in a process known as cell adhesion‐mediated drug resistance (CAM‐DR). We also observed the effect of KD Notch1 on cell survival under high concentrations of doxorubicin treated media. RESULTS: H69AR and SBC‐3 cells expressed Notch1 protein and grew as adherent aggregates, which confer resistance to high concentrations of doxorubicin. On inhibiting Notch1, we observed activation of the apoptotic pathway in cells, possibly resulting from the loss of CAM‐DR and, thus, SBC‐3 cells showed a loss of chemoresistant ability. However, in H69AR cells with KD Notch1, the expression of MRP‐1 was increased and, thus, sustained the chemoresistant ability of cells. CONCLUSION: The Notch1 signaling pathway is involved in mediating the drug resistance phenotype of SCLC cells.